Career readiness, developmental work personality and age of onset in young adult central nervous system survivors. (April 2013) - Strauser, David; Wagner, Stacia; Wong, Alex W. K.; O'Sullivan, Deidre
<x xml:space="preserve">Abstract</x> Purpose: The primary purpose of this paper is to undertake foundational research in the area of career readiness, work personality and age of onset with young adult central nervous system (CNS) survivors. Method: Participants for this study consisted of 43 individuals whose age range from 18 to 30 (M = 21.64, SD = 3.46), an average age of brain tumor onset of 9.50 years (SD = 4.73) and average years off of treatment of 7.25 years (SD = 5.80). Packets were distributed to survivors who were participating in a psychosocial cancer treatment program. Participants completed multiple career instruments and a demographic form. Differences between groups and among the variables were examined and size effect sizes were analyzed. Results: Young adult CNS survivors had significantly lower levels of work personality and career readiness when compared to young adult non-cancer survivors with CNS cancer with those between the ages of 6 and 12 reported significantly lower levels when compared to individuals diagnosed before age 6 and after the age of 13. Conclusions: Young adult CNS survivors at an increased risk for having lower levels of work personality and career readiness then a norm group comparison. Age of onset (between 6 and 12) may be at significant risk factor for developing poor or dysfunctional work and career behaviors.